Prenatal diagnosis of intellectual disability, autosomal dominant 29 with a nonsense pathogenic variant in SETBP1: a case report and literature review - Wei, Zhuo; Yao, Liying; Zhang, Lei; Li, Shanshan; Xu, Meiyi; Wu, Dan; Li, Wen; Chang, Ying (Frontiers in Genetics, 2025)
IntroductionIntellectual disability, autosomal dominant 29 is a rare disorder resulting from pathogenic variants of SETBP1 gene with no specific mutation hotspot identified. Systematic descriptions of new cases are crucial for understanding the genotypic and phenotypic spectrums of the disease.Case presentationA pregnant woman was referred to the prenatal diagnosis center at our hospital because she has an intellectual disability and has previously given birth to a child with intellectual disabilities. Karyotype, CNV-seq and whole-exome sequencing (WES) were employed to investigate the potential genetic issues in the family. The SETBP1 NM_015559.2: c.2425C>T (p.Gln809*) nonsense variant was found in the proband and mother, who were diagnosed with MRD29. Amniocentesis and genetic analysis (CNV-seq and sanger sequencing for mutation site) were performed as fetal cortical abnormalities and subependymal cystic area presented by ultrasonic examination at 25 + 5 gestational weeks. The genetic analysis confirmed the SETBP1 c.2425C>T (p.Gln809*) nonsense mutation in the fetus. The parents terminated the pregnancy at 30 + 4 gestational weeks.ConclusionThe SETBP1 NM_015559.2: c.2425C>T (p.Gln809*) nonsense variant is pathogenic and SETBP1 haploinsufficiency may be associated with fatal cortical abnormalities. More prenatal clinical data is helpful for a better productive decision making and patient management.